2016
DOI: 10.1002/star.201600161
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of starch‐based films produced using glycerol and 1‐butyl‐3‐methylimidazolium chloride as combined plasticizers

Abstract: The structure and property of cassava starch-based films, produced by using 1-butyl-3methylimidazolium chloride ([BMIM]Cl) and glycerol as combined plasticizers, were investigated. The combined plasticizers exhibited a stronger effect on the disruption of starch granules compared with glycerol as observed by scanning electron microscopy (SEM). When the mass ratio of [BMIM]Cl/glycerol used was 15/15, all the starch granules were disrupted and transferred to a continuous phase. Due to the strong plasticization e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 47 publications
(54 reference statements)
3
18
0
Order By: Relevance
“…In contrast to glycerol-plasticized starch films [7,59], the use of [emim + ][Ac -] as plasticizer leads to an increase in the elongation at break of the films which could be useful for their future applications. Similar results have been found with other ILs such as 1-butyl-3-methylimidazolium chloride [64]. Crystallinity of the film is also related to its mechanical behavior.…”
Section: Accepted Manuscriptsupporting
confidence: 87%
See 1 more Smart Citation
“…In contrast to glycerol-plasticized starch films [7,59], the use of [emim + ][Ac -] as plasticizer leads to an increase in the elongation at break of the films which could be useful for their future applications. Similar results have been found with other ILs such as 1-butyl-3-methylimidazolium chloride [64]. Crystallinity of the film is also related to its mechanical behavior.…”
Section: Accepted Manuscriptsupporting
confidence: 87%
“…These crystalline domains embedded in the amorphous matrix could be the responsible of the improvement of the mechanical properties. The mechanical properties obtained are similar or even better than those reported in previous works using similar concentrations of [emim + ][Ac -] respect to the starch matrix and other ILs [25][26][27]43,64]. Films obtained from corn and wheat starches showed mechanical properties comparable to other common polymers currently used for food packaging such as low-density polyethylene [44], making these films potential substitutes for these commonly used polymers and potentially reducing the associated environmental hazards.…”
Section: Accepted Manuscriptsupporting
confidence: 75%
“…Similar results have been reported in a study where [Bmim]Cl plasticised cassava starch samples showed a degradation temperature at 255 °C (Ren et al, 2017). It was proposed in the same study that the decrease of thermal degradation temperature is due to starch molecular weight reduction during solution processing.…”
Section: Tgasupporting
confidence: 89%
“…Incorporation of BMIMCl in the PLA blends showed deterioration of thermal stability up to 100 °C difference as compared to the samples without IL. Ren et al . claimed that IL could reduce molecular weight of polymer on solution processing with heat.…”
Section: Resultsmentioning
confidence: 99%